PEMBINAAN AKHLAKUL KARIMAH MELALUI BIMBINGAN DAN KONSELING DI SMK PGRI 1 JOMBANG - Rufiqutis Tasdidi; Jumari Jumari (EL-Islam, 2022)
Abstract: This moral development is very much needed, especially in this millennial era, we are faced with moral and moral cases. If this is ignored, it will destroy the future of the nation. Therefore, schools are the front gate in shaping the character of the nation's children. The focus of this research are: 1. How is the development of morality in SMK PGRI 1 Jombang? 2. How is moral development through guidance and counseling at SMK PGRI 1 Jombang? 3. What are the inhibiting and supporting factors for moral development at SMK PGRI 1 Jombang?. The research uses qualitative methods, the type of field research (Field Research), data collection techniques, namely interviews, observations, and documentation. As for the results of the study, it shows 1. The application of moral character at SMK PGRI 1 Jombang is quite good because the coaching is carried out through self- habituation which reflects the attitude of akhlakul karimah 2. Guidance of morality through guidance and counseling at SMK PGRI 1 Jombang is carried out conditionally. but in its implementation it also prioritizes religious values ​​with the aim of overcoming the problems faced by students and having akhlaq karimah 3. Inhibiting and supporting factors of moral development through guidance and counseling lack of attention between children and their parents and in addition to the supporting focus, the motivation of BK teachers on students about the importance of having good morals.